Conformal η-Ricci solitons within the framework of indefinite Kenmotsu manifolds - Yanlin Li; Dipen Ganguly; Santu Dey; Arindam Bhattacharyya (AIMS Mathematics, 2022)
The present paper is to deliberate the class of ϵ-Kenmotsu manifolds which admits conformal η-Ricci soliton. Here, we study some special types of Ricci tensor in connection with the conformal η-Ricci soliton of ϵ-Kenmotsu manifolds. Moving further, we investigate some curvature conditions admitting conformal η-Ricci solitons on ϵ-Kenmotsu manifolds. Next, we consider gradient conformal η-Ricci solitons and we present a characterization of the potential function. Finally, we develop an illustrative example for the existence of conformal η-Ricci soliton on ϵ-Kenmotsu manifold.